Down-Regulation of Tristetraprolin Expression Results in Enhanced IL-12 and MIP-2 Production and Reduced MIP-3α Synthesis in Activated Macrophages - Ulla Jalonen; Riina Nieminen; Katriina Vuolteenaho; Hannu Kankaanranta; Eeva Moilanen (Mediators of Inflammation)
In inflammation, the post-transcriptional regulation of transiently expressed genes provides a potential therapeutic target. Tristetraprolin (TTP) is of the factors regulating decay of cytokine mRNAs. The aim of the present study was to identify cytokines whose expression is regulated by TTP. We established a TTP knock-down cell line by expressing shRNA against TTP (shTTP cell line). A cytokine antibody array was used to measure cytokine production in macrophages exposed to lipopolysaccharide (LPS). Cytokines IL-6, IL-12, TNF-α, and MIP-2 (a homologue to human IL-8) were expressed at higher levels whereas MIP-3α was produced at lower levels in LPS-treated shTTP cells than in control cells suggesting that the expression of these cytokines is regulated by TTP. The present data provide IL-12, MIP-2, and MIP-3α as novel inflammatory cytokine targets for TTP-mediated mRNA decay and stress the role of TTP in the regulation of the inflammatory process.